Autophagy plays an antiviral defence role against tomato spotted wilt orthotospovirus and is counteracted by viral effector NSs - Zhang, Xingwang; Hong, Hao; Yan, Jiaoling; Yuan, Yulong; Feng, Mingfeng; Liu, Qinhai; Zhao, Yanxiao; Yang, Tongqing; Huang, Shen; Wang, Chunli; Zhao, Ruizhen; Zuo, Wenyu; et al. (MPPOL. Molecular plant pathology on-line, 2024)
Autophagy, an intracellular degradation process, has emerged as a crucial innate immune response against various plant pathogens, including viruses. Tomato spotted wilt orthotospovirus (TSWV) is a highly destructive plant pathogen that infects over 1000 plant species and poses a significant threat to global food security. However, the role of autophagy in defence against the TSWV pathogen, and whether the virus counteracts this defence, remains unknown. In this study, we report that autophagy plays an important role in antiviral defence against TSWV infection; however, this autophagy-mediated defence is counteracted by the viral effector NSs. Transcriptome profiling revealed the up-regulation of autophagy-related genes (ATGs) upon TSWV infection. Blocking autophagy induction by chemical treatment or knockout/down of ATG5/ATG7 significantly enhanced TSWV accumulation. Notably, the TSWV nucleocapsid (N) protein, a major component of the viral replication unit, strongly induced autophagy. However, the TSWV nonstructural protein NSs was able to effectively suppress N-induced autophagy in a dose-dependent manner. Further investigation revealed that NSs inhibited ATG6-mediated autophagy induction. These findings provide new insights into the defence role of autophagy against TSWV, a representative segmented negative-strand RNA virus, as well as the tospoviral pathogen counterdefence mechanism.
Keywords: Viral Nonstructural Proteins; nemoci rostlin; Solanum lycopersicum; autofagie; Tospovirus; Plant Diseases; Autophagy; Nicotiana; tabák; virové nestrukturální proteiny